TOLERANCE INCREASE OF AUTOMATIC WEIGHT MEASURING SYSTEMS ON THE BASIS OF SYSTEMATIC ERROR ELIMINATION - A. V. Skachek; V. L. Solomakho; B. V. Tsitovich; V. A. Skachek; V. A. Shapar (Приборы и методы измерений)
Rising of accuracy of automated weighting systems' functioning can be achieved by identifying and exclusion of systematic errors. Methods of reducing of temperature error's impact and design procedure of thermocompensation elements of strain-gauge bridges are considered.